Agent-based modelling and swarming in urban architecture : simulating urban environment - Gomes, Tiago André Martins (My University, 2016)
The focus of this research is to present a method to understand complexity within our cities from the standpoint of the Social Sciences and Urban Architecture itself while making use of Agent-Based Modelling and Swarm Intelligence computational methods based on simple theoretical models of self-organization to allow the exploration of, otherwise, imperceptible qualities within urban space as a complex network. These methods provide an overview on how the human element in the urban environment behaves in a dynamic way and how the city operates from its core individual entities as an emergent complex system built upon architectural elements and society rules as well as basic human rules of motion. Due to its non-linear approach to these non-linear concepts and principles, the structure of this dissertation takes several moments of exploration throughout its course along with the development of a computer program that keeps up with these constantly evolving principles and immaterial qualities. What is then materialized through the adaptive application are complex abstract shapes that are perceived and translated into context specific non-tangible spatial features. Is a space open or closed? How close or how open? Maybe both? Or time-based features like flow/flux and tendency paths, like positive, negative, constrained, loose, etc. These are some of the expected translations that will take place in the closing statement of this dissertation How these sets of features can be perceived translated and thought upon on a context- specific urban space are the main motivation of this work in a physical and in an abstract manner. Both objectives of this research were fulfilled by providing a constantly developing tool that uses the potential of agent based and swarming models for simulation and urban space analysis and perceive emergent proprieties within urban and social space that are complex by nature as well as to review its potential in the integration with architecture’s cultural techniques and practices.

Resumo: O foco desta investigação é apresentar um método para compreender complexidade nas nossas cidades sob o ponto de vista das Ciências Sociais e da Arquitectura Urbana fazendo uso dos métodos computacionais, Agent-Based Modelling e Swarm Intelligence baseados em modelos teóricos simples de auto-organização para proporcionar a exploração de características, de outra forma imperceptíveis dentro do espaço urbano como uma rede complexa. Estes métodos debruçam-se sobre como o elemento urbano se comporta de forma dinâmica no ambiente urbano, e em como a cidade opera desde as mais básicas entidades individuais, como um sistema complexo construído com base em elementos arquitetónicos e regras sociais como também nas regras básicas de locomoção humana . Devido à sua abordagem não linear a estes processos também não lineares, a estrutura desta dissertação assume momentos de exploração ao longo do seu desenvolvimento em paralelo com o desenvolvimentos de um programa de computador que acompanha estes princípios e características imateriais, em constante evolução. O que é posteriormente materializado através da aplicação são formas complexas abstractas que são percepcionadas e traduzidas em características espaciais não tangíveis mediante contextos específicos. É um espaço aberto ou fechado? Quão fechado ou aberto? Talvez as duas? Ou características temporais como fluxo e percursos de tendência positivos, negativos, apertados, soltos, etc. Estas são algumas das traduções que farão parte da interpretação final desta dissertação. Como estes conjuntos de características podem ser percepcionadas traduzidas e pensadas em contextos urbanos específicos são a principal motivação deste trabalho de uma forma física e abstracta. Ambos os objetivos desta pesquisa foram cumpridos , fornecendo uma ferramenta em constante desenvolvimento que utiliza o potencial dos modelos de agent based e swarming para simulação e análise do espaço urbano e perceber propriedades emergentes no espaço urbano e social que são complexas por natureza , bem como para avaliar o seu potencial na integração com as técnicas e práticas culturais da arquitetura.
Keywords: Agent-Based Model; Swarm Intelligence; Modelo computacional de simulação; Urbanismo